2004
DOI: 10.1002/clc.4960271202
|View full text |Cite
|
Sign up to set email alerts
|

Aortic sclerosis—a marker of coronary atherosclerosis

Abstract: Summary: Aortic valve sclerosis is defined as calcification and thickening of a trileaflet aortic valve in the absence of obstruction of ventricular outflow. Its frequency increases with age, making it a major geriatric problem. Of adults aged > 65 years, 21-29% exhibit aortic valve sclerosis. Incidence of aortic sclerosis increases with age, male gender, smoking, hypertension, high lipoprotein (Lp) (a), high low-density lipoprotein (LDL), and diabetes mellitus. Aortic valves affected by aortic sclerosis conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…Multiple studies support the presence of shared pathologic pathways between calcific AV disease and atherosclerosis 29. Calcific AV disease and atherosclerosis share common risk factors, such as age, smoking, hypertension, hypercholesterolemia, diabetes mellitus, and metabolic syndrome 1, 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies support the presence of shared pathologic pathways between calcific AV disease and atherosclerosis 29. Calcific AV disease and atherosclerosis share common risk factors, such as age, smoking, hypertension, hypercholesterolemia, diabetes mellitus, and metabolic syndrome 1, 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to pathophysiology, it has been proven that early lesions of AVC implicate active processes similar to atherosclerosis, such as lipid deposition, macrophage infiltration, and production of osteopontin as well as other proteins (Rajamannan, 2010). Further changes associated with extracellular matrix remodeling and neovascularization ultimately lead to active calcification (Prasad and Bhalodkar, 2004;Helske et al, 2007). Experimental animal models of AVC (Rajamannan et al, 2005;Drolet et al, 2006) demonstrated that early lesions contained inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Kirsten and his colleagues studied the morphologic classification system for AVS by transesophageal echocardiography and correlated the subtypes of AVS with the presence of cardiovascular disease, and they concluded that it is possible to identify a subgroup of patients with mixed nodular and diffuse sclerosis, were at increased risk for CAD including multivessel disease 14 . In 2006, Serdar et al 15 , studied the association between AVS and the extent of coronary atherosclerosis by means of the Gensini score system, and he concluded that AVS is strongly interrelated with the coronary angiographic results. Echocardiographic detection of AVS in patients undergoing coronary angiography can predict the extent of coronary atherosclerosis 15 .…”
Section: Discussion:-mentioning
confidence: 99%
“…In 2006, Serdar et al 15 , studied the association between AVS and the extent of coronary atherosclerosis by means of the Gensini score system, and he concluded that AVS is strongly interrelated with the coronary angiographic results. Echocardiographic detection of AVS in patients undergoing coronary angiography can predict the extent of coronary atherosclerosis 15 . Another study concluded that pathologic processes that may occur in coronary arteries may be identified more easily in the aortic valve and they suggest that once the diagnosis of AVS has been made by echocardiography, it should be considered as a potential marker of CAD, and patients who are diagnosed with AVS should undergo intensive screening for CAD with aggressive management for modifiable risk factors.…”
Section: Discussion:-mentioning
confidence: 99%